The determinants of macroeconomic variables towards stock market return: case in China / Maizatul Izati Mohd Azizi - Mohd Azizi, Maizatul Izati (2016)
This paper examine the relationship between several macroeconomic variables (Exchange Rate, Money Supply and Industrial production) and Shanghai Stock Exchange Composite Index from year 2007 until year 2014 which is the data was examined based on quarterly data. This paper employs ADF statistic to examine the relationship and the result shows there are relationship between dependent and independent variables. In this paper, data are not normally distributed, so the data cannot be used by the other countries and study is free from autocorrelation problem. The result of this study also indicates that only money supply have significant impact on stock market.